Enhancing leadership capacity in the public sector: branding as an employer of choice. Issue 3 (12th August 2019) - Mau, Tim A.
Abstract : Purpose: Public services around the world are grappling to enhance their leadership capacity. One approach is to provide leadership training and development to public servants, while another would be to target and hire individuals with proven leadership ability. The purpose of this paper is to focus on that latter strategy by critically examining the concept of branding the public service as an employer of choice as a means of recruiting and retaining sufficient leadership capacity. Design/methodology/approach: The paper begins by outlining the challenge faced by governments to recruit the best and brightest employees into the public service. It then reviews the literature on the concept of branding as an employer of choice, including its perceived advantages and limitations, before undertaking a case study analysis of the 2007 public sector branding initiative of the Canadian federal government. Findings: It is very difficult to develop a single, master brand given the diversity and complexity of the hundreds of organizations that comprise the public sector. While it may be a popular concept for private sector organizations, the concept of branding the public sector as an employer of choice has yet to demonstrate its merit. Canada, which was ostensibly the vanguard in terms of public sector branding, has been unable to position the federal public service as an employer of choice. Originality/value: There is very little research on the use of branding as an employer of choice in the public sector. This paper contributes to the knowledge about the limitations of such strategies for ensuring that the public sector has the requisite leadership capacity.